IT Self Efficacy, IT Anxiety dan Minat Menggunakan E-money - Suryani, Delina; Kurniawan, Asep; Umiyati, Indah (Program Studi Akuntansi FPEB UPI, 2020)
Penelitian ini bertujuan untuk mengetahui minat mahasiswa akuntansi dalam menggunakan e-money. Penelitian ini menggunakan Theory of Acceptance Model (TAM) untuk melihat dampak perceived ease of use, perceived of usefulness, attitude toward using, IT self efficacy, dan IT anxiety terhadap minat mahasiswa akuntansi dalam menggunakan e-money. Dengan menggunakan metode convenience sampling, penelitian ini menganalisis 156 mahasiswa akuntansi dan data diolah dengan teknik Structural Equation Modeling (SEM) dan didukung oleh perangkat lunak LISREL 8.80. Hasilnya menunjukkan bahwa minat untuk menggunakan e-money dipengaruhi oleh attitude toward using dan IT self efficacy.Â Abstract. This study aims to find out intentions of accounting student in using of e-money. This research using Theory of Acceptance Model (TAM) to see the effect of perceived ease of use, perceived of usefulness, attitude toward using, IT self efficacy, and IT anxiety that affected behavioral intention to use of accounting student in using of e-money. Using convenience sampling methods this research analyzed 156 accounting students and data is processed with Structural Equation Modeling (SEM) technique and supported by LISREL 8.80 software. The result shows that the behavioral intention to use of e-money affected by attitude toward using and IT self efficacy.